Penerapan Metode Drill Dalam Meningkatkan Kanji Pada Siswa LPK Dwipayana Cipta Karya Ubud Tahun Ajaran 2022 - I Gusti Ayu Niken Launingtia (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
Teaching Japanese especially in learning kanji is very difficult, so the teacher tries the drill method which aims to make it easy for students to remember kanji letters from how to read kanji and how to write the kanji for each stroke and also to find out the obstacles students experience during the kanji learning process. The method used in learning kanji is the Drill method for three weeks. The subjects in this study were 30 students of LPK Dwipayana Cipta Karya located in Bunutan Village, Ubud. The type of data in this study uses quantitative data which is used in calculating the results of students' kanji answers and qualitative data which will be presented by the results of the questionnaire and combined with the results of interviews with teachers and students. Methods and data research techniques in this study, namely using observation before knowing the weaknesses experienced by students at LPK Dwipayana Cipta Karya, then distributing questionnaires related to starch to students, after that conducting interviews with students and teachers regarding the results obtained from the results of the questionnaire. It can be concluded from the results of the analysis that the drill method is very effective in learning kanji for LPK Dwipayana Cipta Karya students. It can be seen from the fact that there are more students who get vulnerable kanji scores of 70-100 than students who get <70 because after receiving kanji training at LPK and not practicing back independently.